Listeria monocytogenes risk associated with chicken at slaughter and biocontrol with three new bacteriophages. Issue 3 (8th January 2019) - Cufaoglu, Gizem; Ayaz, Naim Deniz
Abstract: The aim of this study was to isolate Listeria monocytogenes from chicken neck skins and lytic bacteriophages from poultry slaughterhouse wastewaters, and following the characterization of the isolates, biocontrol of L. monocytogenes was investigated on chicken drumsticks with the isolated phages. L. monocytogenes prevalence was detected 12.3% in the chicken samples and the dominant serotype was determined as 1/2a (92.5%). Expression levels of major virulence genes were revealed by real‐time RT‐PCR. Ten different DNA profiles were detected by ERIC‐PCR fingerprinting. According to the MIC results, LM‐P75 was defined as MDR by showing resistance to antibiotics in six different groups. Besides, five lytic listeriophages were isolated from wastewaters and treated with Cla1 and Sac1 . Taking EoP, TEM, in vitro, and in vivo analyses results into consideration, three bacteriophages were used for the biocontrol assay. The application of the bacteriophages on drumsticks achieved a reduction up to 3.3 log CFU/ml in L. monocytogenes count in 3 hr of incubation at 4°C. Practical applications: Our results showed that in spite of the developments in hygiene practices during slaughtering, chicken meat is still a potential source for L. monocytogenes . On the other hand, the phage cocktail that used in this study can be an effective tool to reduce L. monocytogenes in chicken carcasses at final wash or at cooling step in poultry slaughtering process, as well as in decontamination of chicken meat parts.